Surgical treatment of renal cell carcinoma recurrence at the renal fossa following radical nephrectomy - Jesus, Carlos Márcio Nóbrega de; Casafus, Filemón Anastásio Silva; Agostinho, Aparecido Donizetti (São Paulo Medical Journal, 2008)
CONTEXT: Isolated renal cell carcinoma recurrence at the renal fossa is a rare event. This condition occurs in 1 to 2% of radical nephrectomy cases. It is usually seen in postoperative follow-up imaging examinations such as abdominal computed tomography or abdominal ultrasound. There is controversy among urologists and oncologists regarding the best way to treat this rare situation, because of the few cases in the literature. CASE REPORT: We report on a case of isolated recurrence at the renal fossa due to renal cell carcinoma (RCC), four and a half years after radical nephrectomy, without evidence of metastases in other organs. The diagnosis was made from abdominal tomography performed during outpatient follow-up, in which a retroperitoneal mass was observed in the renal fossa. Excision was carried out by means of a subcostal transversal incision, without complications. One and a half years after the procedure, there was evidence of metastasis in the left lung and, six months later, another recurrence at the ninth anterior right rib, while the patient remained asymptomatic. Aggressive surgical treatment is a good method for controlling this rare situation of single retroperitoneal RCC recurrence. Abdominal tomography must continue to be performed over long periods of follow-up, to monitor for RCC following radical nephrectomy, in order to diagnose any late retroperitoneal recurrences. These must be treated as single RCC metastases.